47.3: Invited Paper: Near IR Transmission System (NITS): LCD Enhancement Films Enabling High Performance Near IR Transparent LCDs. (26th August 2021) - Acharya, Bharat R.; Sousa, Matthew; Fabick, Ryan; Taylor, Robert; Rosen, David; Cole, Matthew; Sanford, Quinn; Long, Shine; Liu, Desmond; Liu, Yang; Chen, Jennifer; Wang, Richens; et al.
Abstract : The conventional light management films used to enhance display performance of a conventional edge‐lit LCD reflect, scatter, and refract both visible and near infrared (IR) light and therefore do not allow imaging though LCDs. We have developed an entirely new class of display enhancement films and coatings that enable imaging through LCDs in near IR wavelengths while maintaining high display quality. To demonstrate application of this Near IR Transmission System (NITS) for near‐field (where the object is in proximity to the imager) imaging, we show under display fingerprint sensing for LCD‐based smart phones. We envision other applications of this technology in both the near‐field and far‐field (where the object is far from imager) regimes.